Identification of the Q Gene Playing a Role in Spike Morphology Variation in Wheat Mutants and Its Regulatory Network - Zhang, Jiazi; Xiong, Hongchun; Guo, Huijun; Li, Yuting; Xie, Xiaomei; Xie, Yongdun; Zhao, Linshu; Gu, Jiayu; Zhao, Shirong; Ding, Yuping; Liu, Luxiang (Frontiers in Plant Science, 2022)
The wheat AP2 family gene Q controls domestication traits, including spike morphology and threshability, which are critical for the widespread cultivation and yield improvement of wheat. Although many studies have investigated the molecular mechanisms of the Q gene, its direct target genes, especially those controlling spike morphology, are not clear, and its regulatory pathways are not well established. In this study, we conducted gene mapping of a wheat speltoid spike mutant and found that a new allele of the Q gene with protein truncation played a role in spike morphology variation in the mutant. Dynamic expression levels of the Q gene throughout the spike development process suggested that the transcript abundances of the mutant were decreased at the W6 and W7 scales compared to those of the WT. We identified several mutation sites on the Q gene and showed that mutations in different domains resulted in distinct phenotypes. In addition, we found that the Q gene produced three transcripts via alternative splicing and that they exhibited differential expression patterns in nodes, internodes, flag leaves and spikes. Finally, we identified several target genes directly downstream of Q, including TaGRF1-2D and TaMGD-6B, and proposed a possible regulatory network. This study uncovered the target genes of Q, and the results can help to clarify the mechanism of wheat spike morphology and thereby improve wheat grain yield.